Comparative Studies of the Smith and Raynaud Strains of Murine Cytomegalovirus - Kim, Kwang Soo (1974)
A number of the biological, biophysical, and immunological parameters of the Smith and Raynaud strains of murine cytomegalovirus were compared. The two strains were found to be indistinguishable.